PELATIHAN LEADERSHIP LIFE SKILL DAN KONSEP DESAIN PRODUK DALAM MEMPERSIAPKAN WIRAUSAHA BAGI SISWA SMA - Ahmad; Aifa Raviva; Tharisya SP (Jurnal Serina Abdimas, 2024)
This activity aims to provide as early an understanding as possible about entrepreneurship and life skills as well as product design by providing examples around you to use as business ideas. Delivery of activities is carried out face to face in the room provided by the partner. The activity is carried out in the form of a lecture, while providing product design examples and analysis is carried out by students as part of the activity presenter team. The participants were very enthusiastic about listening to the lecture materials presented. The results of the activity showed that 89% of the explanations to students were considered very good. Understanding how to capture consumer needs and the design process and entrepreneurship were rated excellent 91%, 67% and 90% respectively by training participants.